FORMULATION AND EVALUATION OF ETHANOLIC EXTRACT OF CRYPTOLEPIS SANGUINOLENTA ROOT TABLETS - SALOME A, CHIME; V.I, ONYISHI; M. A., MOMOH; GODSWILL C., ONUNKWO (Innovare Journal of Ayurvedic Sciences, 2014)
Objectives: To study were to formulate the ethanolic extract of Cryptolepis sanguinolenta root into tablets and to evaluate the effect of different binders and binder concentration on the properties of tablets. Materials and method: The phytochemistry of ethanolic extract of Cryptolepis sanguinolenta was evaluated. The tablets were formulated by wet granulation using gelatin and sodium carboxymethyl cellulose (SCMC) as binders at concentrations of 2 %, 4 %, 6 % and 8 %w/w. The tablets were evaluated using the necessary official and unofficial tests. Results: Phytochemical analysis revealed the presence of alkaloids, terpenoids, steroids, proteins, carbohydrate, resins, reducing sugars and glycosides. Tannins, saponins, flavonoids and acidic compounds were absent. The tablets passed the uniformity of weight test and deviations obtained complied with BP specifications. Tablets disintegration time ranged from 8.00 ± 0.10 to 13.50 ± 0.21 min for tablets formulated with 2 and 4 % gelatin and 10.00 ± 0.17 to 31.00 ± 0.27 min for tablets formulated with 2 and 8 % SCMC. C. sanguinolenta tablets formulated gelatin significantly showed higher hardness values than SCMC (p < 0.05). Tablets showed friability of approximately ≤ 1 %. Conclusion: Therefore, gelatin showed good properties for formulating Cryptolepis sanguinolenta normal release tablets than SCMC.